Animal‐mediated organic matter transformation: Aquatic insects as a source of microbially bioavailable organic nutrients and energy. (6th December 2018) - Parr, Thomas B.; Capps, Krista A.; Inamdar, Shreeram P.; Metcalf, Kari A.
Abstract: Animal communities are essential drivers of energy and elemental flow in ecosystems. However, few studies have investigated the functional role of animals as sources of dissolved organic matter (DOM) and the subsequent utilization of that DOM by the microbial community. In a small forested headwater stream, we tested the effects of taxonomy, feeding traits, and body size on the quality and quantity of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) excreted by aquatic insects. In addition, we conducted steady‐state solute additions to estimate instream demand for labile C and compared it to the C excreted by invertebrates. Individual excretion rates and excretion composition varied with body size, taxonomy and feeding guild. The estimated average community excretion rate was 1.31 μg DOC· per mg insect dry weight (DW) −1  hr −1 and 0.33 μg DON·mg DW −1  hr ‐1, and individuals excreted DON at nearly twice the rate of NH 4 + . This DOM was 2–5 times more bioavailable to microbial heterotrophs than ambient stream water DOM. We estimated that the insect community, conservatively, excreted 1.62 mg of bioavailable DOC·m −2  hr −1 and through steady‐state additions measured an ambient labile C demand as 3.97 ± 0.67 mg C m −2  hr −1 . This suggests that insect‐mediated transformation and excretion of labile DOC could satisfy a significant fraction (40 ± 7%) of labile C demand in this small stream. Collectively, our results suggest that animal excretion plays an essential functional role in transforming organic matter into microbially bioavailable forms and may satisfy a variable but significant portion of microbial demand for labile C and N. A plain language summary is available for this article. Abstract : Plain Language Summary